(3eONd fXQj hJWHjbjs - (3MejO YHO GdfHj(B, (3GdWGFjs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2008)
- (3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B: (3fXGe GdeYdheGJ GdJShjbjI fXGe GdeYdheGJ GdJShjbjI ,ebOeI aj GdHMK GdJShjbj,,NWhGJ EYOGO GdHMK GdJShjbj(B.(3GdGWGQ GdejOGfj dHMhK GdJShjb s
(3HjHdjhZQGajG fgGjI cd aUd ; edGMb fgGjI cd aUd s
Keywords: (3GdJShjbs